Excision of specific DNA-sequences from integrated retroviral vectors via site-specific recombination. - Bergemann, J (1995)
Vectors for gene transfer and gene therapy were developed which combine the advantages of the integrase and recombinase systems. This was achieved by inserting two loxP sites for specific DNA excision into an MESV based retroviral vector. We show that this 'retroviral lox system' allows the infection of cells and the expression of transferred genes. In addition, we constructed an efficient retrovirus-based expression system for a modified Cre recombinase. Functional tests for DNA excision from integrated retroviral lox vectors were performed by the use of a negative selectable marker gene (thymidine kinase). Cre expression in cells infected with retroviral lox vectors and subsequent BrdU selection for cells in which site-specific recombination has occurred results in large numbers of independent cell clones. These results were confirmed by detailed molecular analysis. In addition we developed retroviral suicide vectors in which the enhancer/promoter elements of both LTRs were replaced by lox sequences. We show that lox-sequences located in the LTRs of retroviral vectors are stable during retroviral replication. Potential applications of this system would be the establishment of revertants of retrovirus-infected cells by controlled excision of nearly the complete proviral DNA.